2003
DOI: 10.21273/jashs.128.2.0188
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Resistance to Two-spotted Spider Mite and Glandular Leaf Trichomes in Wild Tomato Lycopersicon pimpinellifolium (Jusl.) Mill.

Abstract: Genetics of resistance to Tetranychus urticae Koch and of glandular trichomes of Lycopersicon pimpinellifolium accession TO-937 in a cross between susceptible L. esculentum Mill. `Moneymaker' and resistant TO-937 was studied in a greenhouse experiment. Parents, F1, F2, and two BC1 generations, interspersed with susceptible tomato plants to avoid negative interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 32 publications
3
28
0
2
Order By: Relevance
“…However, problems related to negative interplot interference, due to the high frequency of resistant genotypes observed in that assay, hindered the precise calculation of the number of genes responsible for this trait. Later, we improved the pest resistance test by interspersing susceptible tomato plants between the tested ones and results obtained indicated that pest resistance might be controlled by a single dominant major locus although it could be additionally modulated by unknown minor loci (Fernandez-Muñoz et al 2003). We have confirmed these previous results indicating that resistance to spider mite in TO-937 should be governed by a major locus, the Rtu2.2 QTL located in the telomere of chromosome 2.…”
Section: Discussionsupporting
confidence: 70%
See 4 more Smart Citations
“…However, problems related to negative interplot interference, due to the high frequency of resistant genotypes observed in that assay, hindered the precise calculation of the number of genes responsible for this trait. Later, we improved the pest resistance test by interspersing susceptible tomato plants between the tested ones and results obtained indicated that pest resistance might be controlled by a single dominant major locus although it could be additionally modulated by unknown minor loci (Fernandez-Muñoz et al 2003). We have confirmed these previous results indicating that resistance to spider mite in TO-937 should be governed by a major locus, the Rtu2.2 QTL located in the telomere of chromosome 2.…”
Section: Discussionsupporting
confidence: 70%
“…At this stage, 18 S. pimpinellifolium resistant parental plants, 18 F 1 Theor Appl Genet plants and the segregating plants were transplanted to soil in a plastic-house following a random distribution in which all these plants were surrounded by control susceptible plants of cv. Moneymaker as we previously described (Fernandez-Muñoz et al 2003). The transplants were placed 0.4 m apart in a row whereas distance between rows was 1 m. Plants were watered at 3-to 4-day intervals and fed with soluble fertilizer once a week.…”
Section: Plant Materialsmentioning
confidence: 99%
See 3 more Smart Citations